2022
DOI: 10.1029/2021jg006775
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Scaling Effect on Gross Primary Productivity Estimation in the Upscaling Process of Surface Heterogeneity

Abstract: Surface heterogeneity aggregation from medium to coarse resolutions (e.g., 240-960 m) may be the largest source of gross primary productivity (GPP) scaling errors • A big gap in "correcting scaling errors (lowest)" and "causing scaling errors (highest)" was observed for the elevation information • Several practical strategies for large-scale GPP estimation over mountainous areas were suggested based on the findings in this work

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 81 publications
(120 reference statements)
0
7
0
Order By: Relevance
“…Different from these ESMs, BEPS‐TerrainLab assigns various biophysical parameters at the pixel level, which is an effective tool to obtain fine spatial resolution estimates (e.g., 30 m). The BEPS‐TerrainLab model has been used by many investigators as an effective tool in analyzing vegetation productivity in mountain ecosystems (Chen et al., 2013; Govind et al., 2011; Sonnentag et al., 2008; Xie et al., 2021, 2022, 2023). Over the past decades, BEPS has also been successfully employed to obtain carbon and water fluxes at the national‐scale (Y. Liu et al., 2014; Zhou et al., 2007), continental‐scale (Matsushita & Tamura, 2002; Sprintsin et al., 2012), and the global scale (Chen et al., 2012, 2019; L. M. He et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Different from these ESMs, BEPS‐TerrainLab assigns various biophysical parameters at the pixel level, which is an effective tool to obtain fine spatial resolution estimates (e.g., 30 m). The BEPS‐TerrainLab model has been used by many investigators as an effective tool in analyzing vegetation productivity in mountain ecosystems (Chen et al., 2013; Govind et al., 2011; Sonnentag et al., 2008; Xie et al., 2021, 2022, 2023). Over the past decades, BEPS has also been successfully employed to obtain carbon and water fluxes at the national‐scale (Y. Liu et al., 2014; Zhou et al., 2007), continental‐scale (Matsushita & Tamura, 2002; Sprintsin et al., 2012), and the global scale (Chen et al., 2012, 2019; L. M. He et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Xie et al. (2022) suggested that different climatic characteristics might lead to different levels of water and radiation redistributions. To capture the combined effect of climatic factors and topography on GPP estimation, TCI clim is modeled as: normalTnormalCInormalcnormallnormalinormalm=fnormalcnormallnormalinormalm()Prenormalgnormals,normalRnormaladnormalgnormals $\mathrm{T}\mathrm{C}{\mathrm{I}}_{\mathrm{c}\mathrm{l}\mathrm{i}\mathrm{m}}={f}_{\mathrm{c}\mathrm{l}\mathrm{i}\mathrm{m}}\left(\mathrm{Pr}{\mathrm{e}}_{\mathrm{g}\mathrm{s}},\mathrm{R}\mathrm{a}{\mathrm{d}}_{\mathrm{g}\mathrm{s}}\right)$ where f clim (*) is a function of the total precipitation (Pre gs ) and average daily radiation (Rad gs ) during growing season.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wu et al (2022) evaluated bottom-up scaling across multiple products for global soil nitrous acid (HONO) emissions. Levy et al (2022) reviewed the key challenges for upscaling when it comes to the UK greenhouse gas program and finds an essential role for uncertainty propagation, a factor also evaluated for gross primary productivity upscaling by Xie et al (2022). For comparing to top-down measurements, such as flux towers to satellites, source areas and (non-)linearities in downscaling need to be taken into account, whether that is for carbon emissions in a salt marsh (Hill & Vargas, 2022), hotspots of methane in eddy covariance flux tower footprints (Rey-Sanchez et al, 2022), or land surface temperature over heterogeneous landscapes (Desai, Khan, et al, 2021).…”
Section: A Scale For All Silosmentioning
confidence: 99%